The impact of the COVID-19 pandemic on household financial well-being - Sami N. M. Abushammala (Global Business & Finance Review (GBFR), 2022)
Purpose: The current research is one of the few studies investigating the impact of COVID-19 on shattered house- holds' financial well-being in light of Friedman's Theory of Consumption Function. It explored if there are statistical differences in the impact of COVID-19 due to the demographic variables of the study. Design/methodology/approach: The study is descriptive and analytical. It used an online survey that targeted respondents representing 387 Palestinian households randomly selected from the community of the Gaza Strip. Findings: The results showed a negative impact of the COVID-19 pandemic on households' financial well-being. It also revealed these households' lack of financial resilience due to the combined effect of the pandemic and the concurrent siege and its economic drawbacks. The statistical results demonstrated no statistically significant differences in the households' mean financial well-being scores due to gender before and during the COVID-19 pandemic. In contrast, it was found that there are statistically significant differences in the households' mean scores of financial well-being due to the (education level, number of household members, employability status, and the number of households' breadwinners) before and during the COVID-19 pandemic. Research limitations/implications: The researcher conducted an online survey among the general population in the Gaza Strip during the COVID-19 pandemic between the 2nd and 5th of June 2021. Although the results of this study are based on the Palestinian context, the main hypotheses can be tested in other countries to assess the impact of COVID-19 on household financial well-being, especially in emerging countries. Originality/value: This study is the first to address the financial and economic effects of the COVID-19 pandemic on households already shattered and torn by suffrage political and economic inequalities. It also demonstrates how people in emergencies tend to respond to the resulting conditions of the pandemic in the light of Friedman's Theory of the Consumption Function.
Keywords: 650; COVID-19 pandemic; Financial Well-being; Households; Financial resilience; Financial conditions; Friedman Theory of Consumption Function